Pullout behavior of straight and hooked-end steel fibers in UHPC matrix with various embedded angles. (10th December 2018) - Qi, Jianan; Wu, Zemei; Ma, Zhongguo John; Wang, Jingquan
Highlights: The effect of the inclination angle on the pullout behavior of steel fibers in UHPC is investigated. The percentage of end hook contribution to total pullout energy ranges from 50% to 56.8%. The pullout response of a fiber with an embedded angle of 0º could be adopted for safety consideration. Two new indices are proposed to evaluate the fiber-matrix interfacial bond behavior. Abstract: The study provided a systematic evaluation of the pullout behavior of straight and hooked-end steel fibers embedded in ultra-high performance concrete (UHPC) with various angles using a single fiber pullout test. Three steel fibers, including one straight fiber and two hooked-end fibers, were aligned at 0°, 30°, and 45° with respect to the loading direction. The fibers were pulled out from non-fiberous UHPC matrix with a compressive strength of 151.5 MPa. Experimental results showed that when the fiber embedded angle increased from 0° to 30° and 45°, the average bond strengths of straight fibers were increased by 19.2% and 52.9%, while the average bond strengths of hooked-end fibers were increased by 10.3–13.6% and 16.2–26.1%, respectively. The percentage of end hook contribution to total pullout energy ranged from 50% to 56.8%, indicating significant mechanical anchorage contribution. Two types of fiber failure modes, including fiber pullout failure and fracture failure, were found, depending on fiber angles. From Scanning Electronic Microscopy (SEM) observation, interfacial transition zone failure, fiber surface scratching, and matrix failure were identified. Two new indices, namely energy dissipation index and bond strength index, were proposed to evaluate the fiber-matrix bond behavior. It was found that hooked-end fibers with a smaller diameter could be a better choice for structural application according to the proposed evaluation indices. The proposed indices offered an alternative and practical method to assess the fiber-matrix bond behavior.